Rabies encephalitis or post-vaccination encephalitis in a pregnant woman with a surviving premature neonate - Tapia-Pérez, Rafael (2022)
Human rabies is a serious infection that requires application of rabies serum and vaccine, which can cause post-vaccination acute demyelinating encephalomyelitis (ADEM). We report a 27-year-old pregnant woman who has been bitten by a dog on her right hand. She didn’t receive rabies serum but she received 5 vaccinations. With last vaccination she presents hand numbness, malaise, fever, hydrophobia, altered consciousness. A cesarean section was performed and the patient was induced a therapeutic coma. Nape skin biopsy and inoculation in mice were negative, while seroneutralization in mice and detection of anti-rabies antibodies were positive. In umbilical cord, mouse seroneutralization was positive. Magnetic resonance imaging revealed lesions compatible with ADEM. By some criteria, it could be rabies; however, the chart would be more compatible with ADEM.